CONCEPTUAL LEVEL STRATEGY RECOMMENDATIONS FOR UNDERSTANDING MARKETING COMMUNICATION EFFORTS IN DIGITAL CONSUMPTION CULTURE WITH NEUROSCIENCE TECHNIQUE - Ferdi Akbıyık; Ömer Kürşad Tüfekci (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi, 2023)
The increasing complexity of marketing communication efforts in digital consumption culture requires a deeper understanding and measurement of their impact. Neuroscience techniques have become essential in this regard, and this paper proposes conceptual level strategy recommendations for understanding marketing communication efforts using such techniques. The paper recommends the use of neuromarketing research methods, such as EEG, fMRI, and eye-tracking, to gain insights into consumer behavior and preferences. Besides, the paper also suggests the use of cross-cultural research methods to account for cultural differences in consumer behavior and preferences. Moreover, the paper proposes integrated marketing communication strategies that leverage multiple channels to effectively reach consumers in digital consumption culture, such as social media marketing, content marketing, and mobile marketing. Overall, these conceptual level strategy recommendations provide a framework for better understanding and measuring the impact of marketing communication efforts in digital consumption culture using neuroscience techniques. By following these recommendations, marketers and researchers can develop more effective marketing strategies and gain a deeper understanding of consumer behavior and preferences in this context.